Listening for Airborne Sound of Damage: A New Mode of Diagnostic Imaging - Bernhardt, Yannick; Solodov, Dmitry; Müller, Dieter; Kreutzbruck, Marc (Frontiers in Built Environment, 2020)
Resonant air-coupled emission (RACE) is a new method of detecting damage based on local damage resonance (LDR). Resonant vibrations in defect excite airborne acoustic wave, which emanates from the damaged area, and therefore could be used for diagnostic imaging. A conventional approach to RACE imaging uses C-scanning of flat surfaces with a microphone and provides high resolution imaging in the near field zone. In this paper, some features of RACE field are studied experimentally to recognize the possibility of imaging in transition zone between the near- and far-fields. A modification of the RACE scanning mode by using a robot is investigated to be applied to complex shape components. An alternative imaging technique proposed uses a microphone array and provides full-field visualization of RACE field. The 64 microphone acoustic camera array is applied for express testing and imaging. Multiple case studies are given to demonstrate the potential of the both modes for diagnostic imaging of simulated and realistic defects in polymers and composite materials.